COMPARATIVE ANALYSIS OF UNIVERSITY IMAGE BETWEEN MALE STUDENTS AND FEMALE STUDENTS (CASE STUDY MANADO SAM RATULANGI UNIVERSITY) - Awuy, Jillie Eunike; Tielung, Maria V.J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The image of the university is described as an overall impression made in the minds of the public about an organization. Can also define that the university is the result of character and identity of all aspects contained in the university that can be assessed by the community. A positive of university image is one of the absolute things that needs to be built in a company. Image is needed to change the way consumers perceive a company. The image of higher education can be built by providing an overview of what is experienced and felt after using the company's products / services.The aim of this study is to know the difference of university image between male students and female students based on satisfaction, quality, and reputation. This research is a quantitative research and uses independent sample t-test. The sample size of this research is 110 Students of Manado Sam Ratulangi University  (55 males and 55 female). The results showed that there is no significant difference of university image between male students and female students based on satisfaction, quality and reputation. Sam Ratulangi University Manado must improve all aspects of quality so that students feel satisfied. So that it can support the reputation of Sam Ratulagi University itself. Keywords: university, image, satisfaction, quality, reputation